Raspar a cabeça aumenta o estresse fisiológico em homens durante exercício sob o sol - Leonardo Gomes Martins Coelho (2008)
The purpose of the present study was to test the theory that human hair could represent a barrierto solar radiation, allowing minor physiological indices of heat stress during exercise in a hotenvironment under the sun. Participated in this study 10 male volunteers, inhabitants of tropicalregion, healthy and fit for the practice of physical exercises (25,1 ± 2,5 years old; 176,2 ± 4,0 cmof height; 73,7 ± 6,7 kg of weight; VO2max 56,2 ± 5,3 mL×kg-1×min-1). They had wavy or spiraledhair with a layer of at least three centimeters in thickness in the central head region. Thevolunteers participated in three experimental sessions. On the first day, after anthropometriccharacterization, a test to measure the aerobic capacity was done. After two days of the firstmeeting, individuals started the protocol which had two more experimental situations, compostcontinuous exercise in a treadmill with one hour of duration and intensity to 50% of VO2max. Theinclination of treadmill was maintained at 1% during the entire protocol. First continuousexercise: in the external environment under the Sun, with the natural hair within the specifieddimensions. Second continuous exercise: the volunteers had their hair totally scraped andrepeated the exercise under the Sun. The protocols were separated by at least two days and atmost a week. The environmental heat stress was measured by the Index of Wet Bulb GlobeTemperature (WBGT) in º C and used as a co-variable if necessary. A physiological strain index(PSI), rectal temperature, heart rate (HR) and total rate of sweating was measured. The resultsshowed greater PSI (ANCOVA, F = 5222, p = 0,035), greater delta of HR (ANCOVA, F =29009, p = 0,0001) and greater total sweating rate (7,08 ± 0,25 vs. 7,67 ± 0,26, p = 0,30) in thesituation with scraped hair. In conclusion, scratch the head increases the physiological stressindex, variation in heart rate and total sweat hate.